Sporadic ovarian sex cord-stromal tumor with annular tubules: a rare case report - Patel, Krutika; Painter, Devang; Bhagat, Vashudha M.; Shah, Pinkal (International Journal of Research in Medical Sciences, 2019)
Ovarian sex cord stromal tumor with annular tubules (SCTAT) is a distinctive, rare subtype of sex cord stromal tumor of the ovary, predominant component of which has morphological features intermediate between that of granulosa cell and sertoli cell. The majority of ovarian SCTAT are benign. So far, malignant behavior in SCTAT has been reported only in sporadic cases. We have presented a case of SCTAT in a 40 year old lady with no association of Peutz-Jegher (P-J) syndrome. The patient’s chief complaints were post-menopausal bleeding for 1 year on and off along with menorrhagia. MRI abdomen was suggestive of intensely enhancing solid tissue mass lesion in the right adnexa, features suggestive of ovarian mass. Panhysterectomy was done. Grossly uterus and left adnexa appeared to be normal. Right ovary showed mass measuring 17x11x9cm3 in size, on cut section, solid, homogenous lobulated, yellowish areas identified. Microscopic and Immunohistochemistry findings confirmed the diagnosis of sex cord stromal tumor with annular tubules of granulosa cell type. PAS stain supported the diagnosis.